Radar Absorbing Material (ram) and its Effects on the Radar Detection Range - Ismail M. Jaber; Huda I. Hammed (Journal of Madenat Alelem University College, 2013)
The Radar Cross Section (RCS) has been reduced four techniques: Shaping, Radar Absorbing Material (RAM), Passive cancellation and Active cancellation. The RAM is a technology uses in camouflage application mainly in defense. The aim of this technology based on uses materials able upon absorbing the radar. The material consists of different composites consists of Polyaniline (PANI) Based on Nitrile Rubber (NBR) to produce RAMs. Permittivity of these materials is a fundamental to all other calculation. The calculation by used the cavity perturbation method in the X band (8-12 GHz), then, design four layers of the radar absorbing material backed with PEC (such a structure is typically Radar absorbing material RAS). Main goal of this design is tradeoff between low Reflection coefficients, structure thickness, the obtained results for the RC= -12.2 dB in the 12 GHz.